A Conceptual Model on Fee Perception and Quality of Management Education using ISM and Fuzzy MICMAC Analysis - Singh, Archana; Kazi, Roshan; Divekar, Rajiv (Prabandhan: Indian Journal of Management, 2019)
Purpose: The purpose of this paper was to understand the existing relationship between perceptions of fee appropriateness and quality of management education. Using extant literature, we made an attempt to understand the relationship among variables, which was missing in extant literature and proposed a conceptual framework using ISM (interpretive structural modelling). Further, the variables were also categorized using MICMAC analysis. Design: The research procedure was methodically framed. It comprised of primary as well as secondary data & information. We used interpretative structural modelling (ISM) as a tool to understand the linkages and relation among the variables. We used systematic literature review (SLR) method to find the variables from the present literature and further used fuzzy MICMAC analysis to understand the composite balance amid the variables. Findings: The findings using ISM modeling indicated three levels. The output suggested that Fee Appropriateness and Infrastructure were the most significant factors, the second level of the model is Skills Acquired and Career Aspiration, and the third level is Academic Excellence and Institutional Factors. In order to ensure the attainment of high level of management education, the educational institutions may focus their attention on academic excellence, good infrastructure, positively focusing on enhancing institutional features, and skill development of students to fulfill their career aspirations. The fuzzy MICMAC output suggests Fee Appropriateness and Career Aspiration were the dependence variables. Academic Excellence and Institutional Features were the linkage variables and Skills Acquired and Infrastructure were the driving variables. Research Limitations: The study was based on expert opinion; hence, the potential to capture unique insights was limited. Limited variables were also considered for the ISM model. The application in a real situation would need some changes. Originality/Value: It is the first study to propose a conceptual model on Fee Appropriateness for management education using ISM. This research showed the analysis of Fee Appropriateness and its influence on quality of management education.